1965
DOI: 10.1002/jsfa.2740160703
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomere length of free and restrained bovine muscles at low temperature as related to tenderness

Abstract: Tenderness of semitendinosus and psoas major bovine muscles was markedly affected by: ( I ) allowing the muscle to undergo rigor mortis and the associated contraction, following pre-rigor excision, or by ( 2 ) pre-rigor excision followed by restraint in a stretched state while the muscle undergoes rigor mortis. The extent of stretch or contraction induced by pre-rigor treatment was reflected by the sarcomere length. The average sarcomere length of the semitendinosus and psoas major muscles differed widely whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
1

Year Published

1967
1967
1994
1994

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(57 citation statements)
references
References 15 publications
5
51
1
Order By: Relevance
“…Moreover, psoas muscle, which is a very tender muscle, had con siderably longer sarcomere lengths than semiteiidinosus, which is nearly always less tender than the psoas. If the muscle was restrained to pre vent post-mortem shortening, a wide variation in sarcomere lengths was found, even though the muscle had been given & uniform treatment» These results of Herring e^ (1965) may be easily explained by Marsh and Leet's (1966) finding that, in muscle held at fixed length, different rates of cooling in different parts of the muscle cause the more rapidly cooled areas to shorten considerably, whereas other areas in the same muscle lengthen a compensatory amount. Fibers on the exterior of the re strained muscles in Herring's study probably underwent extensive shorten ing since they were cooled rapidly.…”
Section: Umentioning
confidence: 86%
See 2 more Smart Citations
“…Moreover, psoas muscle, which is a very tender muscle, had con siderably longer sarcomere lengths than semiteiidinosus, which is nearly always less tender than the psoas. If the muscle was restrained to pre vent post-mortem shortening, a wide variation in sarcomere lengths was found, even though the muscle had been given & uniform treatment» These results of Herring e^ (1965) may be easily explained by Marsh and Leet's (1966) finding that, in muscle held at fixed length, different rates of cooling in different parts of the muscle cause the more rapidly cooled areas to shorten considerably, whereas other areas in the same muscle lengthen a compensatory amount. Fibers on the exterior of the re strained muscles in Herring's study probably underwent extensive shorten ing since they were cooled rapidly.…”
Section: Umentioning
confidence: 86%
“…Shortening to less than 40% of rest length apparently causes disruption of Z-lines and other structural elements which hold the sarcomeres in proper juxtaposition; this results in increased tenderness. Marsh and Leet's (1966) findings also offer a simple explanation for the results of Herring ^ (1965). These investigators found that o o muscle excised pre-rigor and stored at either 1 or 5 had sarcomere lengths 50% shorter than muscle excised post-rigor, and furthermore that muscle excised post-rigor was always more tender than muscle excised pre-rigor.…”
Section: Umentioning
confidence: 94%
See 1 more Smart Citation
“…It has been suggested that the tenderness of meat removed from the carcass in a pre-rigor condition is highly dependent upon the extent of the cold shortening that occurs after excision (Herring et al, 1965a;Marsh and Leet, 1966). Some muscles, including the LD, which is firmly anchored to the skeleton at one end only, are capable of shortening in the carcass under vertical suspension such as found in normal processing procedures because of tension release (Herring et al, 1965b;Marsh and Leet, 1966 and that sarcomere length is only an indication of molecular changes occurring in the actin and myosin of the muscle fiber (Herring et al, 1965a).…”
Section: Introductionmentioning
confidence: 99%
“…Some muscles, including the LD, which is firmly anchored to the skeleton at one end only, are capable of shortening in the carcass under vertical suspension such as found in normal processing procedures because of tension release (Herring et al, 1965b;Marsh and Leet, 1966 and that sarcomere length is only an indication of molecular changes occurring in the actin and myosin of the muscle fiber (Herring et al, 1965a). …”
Section: Introductionmentioning
confidence: 99%